International financial reporting standards : - Greuning, Hennie van (The World Bank, 2009)
International Financial Reporting Standards (IFRS) in a business situation can have a significant effect on the financial results and position of a division or an entire business enterprise. "International Financial Reporting Standards: A Practical Guide" gives private or public sector executives, managers, and financial analysts without a strong background in accounting the tools they need to participate in discussions and decisions on the appropriateness or application of IFRS. Each chapter summarizes an International Financial Reporting Standard, following a consistent structure: problems addressed by the IFRS; scope of the Standard; key concepts and definitions; accounting treatment; presentation and disclosure; and, financial analysis and interpretation.